Adipocyte heterogeneity and tumor infiltration of adipose tissue in patients with metastatic breast cancer - Hava Izci; Gitte Zels; Anirudh Pabba; Marion Maetens; François Richard; Maxim De Schepper; Josephine Van Cauwenberge; Ha-Linh Nguyen; Kristien Borremans; Sophia Leduc; Karen Van Baelen; Sigrid Hatse; et al. (Breast)
Background: The adipose tissue may serve as a source of energy supporting cancer growth and metastasis. Our understanding of the adipocytes which compose the adipose tissue in different anatomical locations of the body as well as potential microscopic tumor infiltration in patients with metastatic breast cancer remains limited. This study therefore investigates regional variations in adipocyte size and adipose tissue tumor infiltration in patients with metastatic breast cancer. Methods: Within the UPTIDER rapid autopsy program, (NCT04531696), 94 adipose tissue samples from subcutaneous, visceral, retroperitoneal, and mammary depots of 22 patients with metastatic breast cancer were collected and analyzed. Distant adipocyte size was quantified using digital pathology, and tumor infiltration was assessed histologically. Linear mixed quantile regression analyzed the associations between adipocyte size, fat depot type and major histological subtypes. Results: Distant adipocyte size did not significantly differ across fat depots. A trend towards smaller adipocytes in mammary fat at autopsy versus diagnosis was observed, suggesting potential age and/or treatment effects. Adipocyte size correlated positively with BMI at death, especially in subcutaneous and visceral fat. Visceral fat exhibited higher tumor infiltration, notably in patients with invasive lobular carcinoma (ILC). Conclusion: This study highlights the relatively uniform adipocyte size across fat depots in patients with metastatic breast cancer, with potential changes in mammary adipocytes over the disease course. The microscopic tumor cell infiltration observed in the visceral fat, mainly for ILC, underscores the need to undertake additional research to understanding the contribution of the adipose tissue in breast cancer metastasis.